Aryl Radical Selectivity in Biphasic Systems - Altmann, Lisa-Marie; Fürst, Michael; Gans, Eva; Zantop, Viviane; Pratsch, Gerald; Heinrich, Markus (Organic Letters, 2020)
Aryl radicals generated in the aqueous phase of biphasic mixtures have-regardless of a comparably low polarity- A strong preference to react with aromatic substrates in the aqueous phase and not to undergo phase-transfer into a lipophilic phase, independent from the presence of a surfactant. These results represent an important prerequisite toward future studies in biological systems, which typically consist of various compartments of either hydrophilic or lipophilic character.
CRIS-Team Scopus Importer:2020-02-04

Radical arylation of tyrosine residues in peptides - Fehler, Stefanie; Pratsch, Gerald; Östreicher, Christiane; Fürst, Michael; Pischetsrieder, Monika; Heinrich, Markus (Tetrahedron, 2016)
The radical arylation of the phenolic side chain of tyrosine in peptides was investigated. Aryl radicals were generated from aryldiazonium salts using titanium(III) chloride as stoichiometric reductant. Due to the high selectivity with which 3-aryltyrosine derivatives were formed, this reaction type represents a new strategy for the direct functionalization of peptides.
Keywords: Arylation; Diazonium; Peptide; Radical reaction; Tyrosine

Regioselective Radical Arylation of 3-Hydroxypyridines - Fürst, Michael; Bock, Leonard; Heinrich, Markus (Journal of Organic Chemistry, 2016)
The titanium(III)-mediated radical arylation of 3-hydroxypyridines was found to proceed with high regioselectivity for the 2-position. Using aryldiazonium chlorides, which were prepared from the corresponding anilines, as aryl radical sources, a range of 3-hydroxy-2-phenylpyridines were obtained in moderate to good yields under simple reaction conditions. Reactions of ortho-carboxylic ester substituted phenyldiazonium salts directly provided tricyclic benzopyranopyridinones.